2002
DOI: 10.1021/jm020881f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Further Pyrrolidine trans-Lactams as Inhibitors of Human Neutrophil Elastase (HNE) with Potential as Development Candidates and the Crystal Structure of HNE Complexed with an Inhibitor (GW475151)

Abstract: Described herein is a modern approach to the rapid preparation and evaluation of compounds as potential back-up drug candidates. GW311616A, 1, a derivative of pyrrolidine trans-lactams, has previously been described as a potent, orally active inhibitor of human neutrophil elastase (HNE) for the treatment of respiratory disease. These properties made it a suitable candidate for development. Described here is the discovery of three further derivatives of pyrrolidine trans-lactams, which fulfill the criteria requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…On the other hand, Fig. 3b shows that the S1 pocket was perfectly occupied by ONO-5046, the sulfonyl of ONO-5046 pointed toward the main chain nitrogen atoms of Ser 195 and Gly 193 (the oxyanion hole), and the distances were very fit for good hydrogen bonding for Ser 195 and Gly 193 [31]. Moreover, the carboxyl group oxygen and amide group hydrogen in ONO-5046 formed two hydrogen bonds with the hydroxyl group hydrogen and carbonyl group oxygen of Ser 214, respectively.…”
Section: Hydrogen-bonding Interactionsmentioning
confidence: 99%
“…On the other hand, Fig. 3b shows that the S1 pocket was perfectly occupied by ONO-5046, the sulfonyl of ONO-5046 pointed toward the main chain nitrogen atoms of Ser 195 and Gly 193 (the oxyanion hole), and the distances were very fit for good hydrogen bonding for Ser 195 and Gly 193 [31]. Moreover, the carboxyl group oxygen and amide group hydrogen in ONO-5046 formed two hydrogen bonds with the hydroxyl group hydrogen and carbonyl group oxygen of Ser 214, respectively.…”
Section: Hydrogen-bonding Interactionsmentioning
confidence: 99%
“…The striking serglycin dependency for localization of neutrophil elastase in azurophil granules, despite serglycin independency for localization of the highly similar serine proteases cathepsin G and proteinase 3, prompted us to look for a putative glycosaminoglycanbinding surface in the 3-dimensional structure of murine neutrophil elastase (modeled upon the crystal structure of human neutrophil elastase 31 ). We identified a horseshoe-shaped surface with basic amino acids surrounding the active site of neutrophil elastase (encircled in Figure 6A-B), the same region that was previously proposed to interact with sulfated glycosaminoglycans.…”
Section: A Putative Serglycin-binding Surface Of Neutrophil Elastase mentioning
confidence: 99%
“…In the present study, we demonstrated neutrophil infiltration in a mouse photoaging model following repeated exposure to UVB, without erythema or edema, using NASDCA and in situ zymography with the NE inhibitor GW311616A (GW). GW is known to be a highly specific inhibitor of NE (IC 50 : NE, 0.022 mM; tripsin, >100 mM; chymotrypsin, 4.2 mM; cathepsin G, >100 mM) [11]. As noted above, GW would inhibit nearly 100% of the NE; however, GW only reduced the elastase activity to 20%, as shown in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Reaction buffer containing 40 mg/mL DQ-elastin (soluble bovine neck ligament elastin labeled with BODIPY FL dye) was transferred to skin sections, followed by incubation for 24 h at 37 8C. A specific NE inhibitor (GW311616A; Sigma, St. Louis, MO, USA) [11] was used to determine the contribution of NE activity to the observed proteolytic activity. Elastase activity was subsequently detected by fluorescence microscopy (Em/Ex = 505/515 nm) (OLYMPUS, Tokyo, Japan).…”
Section: In Situ Neutrophil Elastase Zymographymentioning
confidence: 99%